2002
DOI: 10.1067/mtc.2002.121291
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory aneurysm of the ascending thoracic aorta

Abstract: alker and colleagues 1 were the first to define the term "inflammatory aneurysm." They reported 19 cases and found that these aneurysms were nonbacterial special types of atherosclerotic aneurysms. Inflammatory aneurysms constitute approximately 5% of all infrarenal abdominal aortic aneurysms. 2 However, location of these aneurysms in the ascending thoracic aorta is extremely uncommon. 3 Connery and colleagues 4 first described an isolated inflammatory aneurysm in the ascending thoracic aorta. Typical histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…During the pathogenesis of aneurysms, activated immune cells have been proposed to contribute to elimination of SMCs, which are a source of ECM proteins, in both AAAs (Henderson et al, 1999) and TAAs (He et al, 2006). Yet, in contrast to AAAs (Paravastu et al, 2009), inflammation is documented in only a few cases in TAAs (Biddinger et al, 1997;Girardi and Coselli, 1997;Roth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…During the pathogenesis of aneurysms, activated immune cells have been proposed to contribute to elimination of SMCs, which are a source of ECM proteins, in both AAAs (Henderson et al, 1999) and TAAs (He et al, 2006). Yet, in contrast to AAAs (Paravastu et al, 2009), inflammation is documented in only a few cases in TAAs (Biddinger et al, 1997;Girardi and Coselli, 1997;Roth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Connery et al 3 published the fi rst report of an isolated infl ammatory aneurysm of the ascending aorta in 1994 and our search of the literature found only seven cases reported to date (Table 1). [3][4][5][6][7][8][9] Seven (88%) of the eight patients, including ours, had symptoms similar to those of an infl ammatory abdominal aortic aneurysm. These symptoms were thoracic pain in six (75%) patients and sudden asystole in one (13%).…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies have shown that CP may also involve other vascular segments, such as the coronary, renal and mesenteric arteries [6][7][8][9][10] and represent, at least in some patients, a systemic vascular process, rather than a localized inflammatory reaction [6] . The presentation of aortic involvement may range from inflammatory aneurism with or without perianeurysmal fibrosis to isolated periaortic (retroperitoneal and/or mediastinal) fibrosis with compression of the aorta [6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of aortic involvement may range from inflammatory aneurism with or without perianeurysmal fibrosis to isolated periaortic (retroperitoneal and/or mediastinal) fibrosis with compression of the aorta [6][7][8][9] . This patient had an aneurysmal form of CP (PRF) with extensive thoracic and abdominal periaortic involvement, which is extremely uncommon.…”
Section: Discussionmentioning
confidence: 99%